CATS: The Hubble Constant from Standardized TRGB and Type Ia Supernova Measurements - D. Scolnic; A. G. Riess; J. Wu; S. Li; G. S. Anand; R. Beaton; S. Casertano; R. I. Anderson; S. Dhawan; X. Ke (The Astrophysical Journal Letters, 2023)
The tip of the red giant branch (TRGB) provides a luminous standard candle for constructing distance ladders to measure the Hubble constant. In practice, its measurements via edge-detection response (EDR) are complicated by the apparent fuzziness of the tip and the multipeak landscape of the EDR. Previously, we optimized an unsupervised algorithm, Comparative Analysis of TRGBs, to minimize the variance among multiple halo fields per host without relying on individualized choices, achieving state-of-the-art ∼<0.05 mag distance measures for optimal data. Here we apply this algorithm to an expanded sample of SN Ia hosts to standardize these to multiple fields in the geometric anchor, NGC 4258. In concert with the Pantheon+ SN Ia sample, this analysis produces a (baseline) result of H _0 = 73.22 ± 2.06 km s ^−1 Mpc ^−1 . The largest difference in H _0 between this and similar studies employing the TRGB derives from corrections for SN survey differences and local flows used in the most recent SN Ia compilations that were absent in earlier studies. The SN-related differences total ∼2.0 km s ^−1 Mpc ^−1 . A smaller share, ∼1.4 km s ^−1 Mpc ^−1 , results from the inhomogeneity of the TRGB calibration across the distance ladder. We employ a grid of 108 variants around the optimal TRGB algorithm and find that the median of the variants is 72.94 ± 1.98 km s ^−1 Mpc ^−1 with an additional uncertainty due to algorithm choices of 0.83 km s ^−1 Mpc ^−1 . None of these TRGB variants result in an H _0 of less than 71.6 km s ^−1 Mpc ^−1 .